The relationship between bullying victimization and gambling among adolescents. Issue 1 (2nd January 2020) - Grande-Gosende, Aris; Richard, Jérémie; Ivoska, William; Derevensky, Jeffrey
ABSTRACT: Victims of bullying are more likely to exhibit health problems, have declining grades, abuse drugs and alcohol, experience depression and low self-esteem. Although bullying victimization has been associated with a host of negative outcomes, problem gambling is a public health problem that has been neglected in the context of bullying victimization. This research investigated the relationship between high-risk gambling and bullying victimization. Responses about gambling behaviours, risk for problem gambling, and bullying victimization was collected from 7, 045 high-school students (mean age 15 years old). Chi-square analyses were used to explore rates of bullying victimization (i.e. physical, verbal, cyber and indirect) based on gambling frequency and risk for gambling problems. Binary logistic regression analyses were conducted separately for male and female frequent gamblers to predict high-risk gambling based on bullying victimization. Results indicated that verbal bullying and the number of gambling activities one participated in the last year predicted high-risk gambling among males. For females, physical bullying and number of gambling activities predicted high-risk gambling. These results contribute to a better understanding of problem gambling and its relationship with various forms of bullying victimization among youth, with gender differences in the types of bullying victimization related to high-risk for problem gambling.